Combination treatment of doxorubicin and SAR405-loaded chitosan nanoparticles for dual targeted anticancer therapy assessment in A549 lung cancer cell line - Mohammedarfat N K., Alamassi (2023)
Conventional anti-cancer drugs including doxorubicin are associated with high toxicity and non-specific distribution in the body resulting in acute side effects. targeting cancer cell survival pathways like autophagy can be enhanced the effective of therapeutic drugs at low concentration to decrease its side effects. Cancer cells can use autophagy to promote tolerance to the stress caused by anti-cancer agents, leading to resistance induction in advanced tumors. SAR405 is an inhibitor of autophagy activity due to its molecular interactions within the ATP binding site but is prematurely degraded extracellularly, therefore is poorly up taken by cells limiting its use. Chitosan nanoparticles (CNPs) are considered to be biologically degradable, non-toxic, and biocompatible as a drug delivery system to minimize and determine their side effects. In this study, we developed a therapeutic strategy to enhance doxorubicin efficiency while simultaneously inhibiting autophagy, by increasing cellular uptake of SAR405 loaded into CNPs. The synthesized nanoparticles were characterized for hydrodynamic diameters and polydispersity measurements. Encapsulation efficiency and drug loading was then elucidated and subsequent morphological of the nanoparticles were determined by electron microscopy. Cytotoxicity assessment and apoptosis were performed through MTT and Annexin-v apoptosis assays. Following encapsulation, the SAR405-loaded chitosan nanoparticles expanded from 54 nm to 161 nm at 10 μM SAR405, while the polydispersity index increased from 0.11 to 0.31. When cells were treated with IC50 values of doxorubicin and 10 μM of SAR405 encapsulated CNP, approximately 47% reduction in viability of cells were observed in Annexin V-FITC/PI assay, compared to doxorubicin alone. Inhibition of autophagy was shown to decrease the resistance of cancer cells to therapeutic drugs and increase their efficacy at low concentration. This study promises targeting of cancer cell survival pathways can be an effective way to Increasing the efficiency of chemotherapeutic drugs.